2018
DOI: 10.3389/ffgc.2018.00008
|View full text |Cite
|
Sign up to set email alerts
|

Heat Waves Alter Carbon Allocation and Increase Mortality of Aleppo Pine Under Dry Conditions

Abstract: Climate extremes are likely to occur more frequently in the future, including a combination of heat waves and drought. However, the responses of trees to combined stress and their post-stress recovery are not fully understood yet. Therefore, this study investigated the responses of semi-arid Pinus halepensis seedlings to moderate drought, heat and combined heat-drought stress, as well as post-stress recovery. The seedlings were grown under controlled conditions and exposed to two 4-days-long heat periods, reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 88 publications
7
78
1
Order By: Relevance
“…Gauthier et al , 2014). However, an acclimation of leaf respiration to elevated growth temperatures has been reported in many instances (Reich et al , 2016; Drake et al , 2019), and R Shoot has been shown to decline during consecutive heatwaves (Birami et al , 2018). Likely explanations for the early downregulation of R Shoot and R Root that we have found in response to heat stress are: first, reduced respiratory demand due to downregulation of growth and maintenance respiration; second, adenylate restriction caused by ATP turnover decline; and/or third, reduced C availability (O'Leary et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gauthier et al , 2014). However, an acclimation of leaf respiration to elevated growth temperatures has been reported in many instances (Reich et al , 2016; Drake et al , 2019), and R Shoot has been shown to decline during consecutive heatwaves (Birami et al , 2018). Likely explanations for the early downregulation of R Shoot and R Root that we have found in response to heat stress are: first, reduced respiratory demand due to downregulation of growth and maintenance respiration; second, adenylate restriction caused by ATP turnover decline; and/or third, reduced C availability (O'Leary et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3a). We refrained from temperatures above 40°C as tree mortality has been found to strongly increase in Aleppo pine seedlings above this threshold, particularly in combination with drought (Birami et al , 2018). As during a typical heatwave in the Yatir Forest (Tatarinov et al , 2016), vapor pressure deficit (VPD) increased alongside increasing temperature, and this increase was slightly greater in the drought‐treated saplings due to low E (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As several prior laboratory-based studies showed, the HW effect was first noticed at the cellular level, which resulted in a decrease in photosynthetic enzyme activity and low stomatal conductance and had effects on other eco-physiological characteristics Zinta et al, 2014). Recent findings have confirmed that HWs significantly alter plant photosynthesis and respiration (Qu, Chen, Bunce, Zhu, & Sicher, 2018;Rashid et al, 2018), reduce CO 2 uptake (Tatarinov et al, 2016), and lead to the redistribution of carbon and nitrogen in a plant or community (Birami et al, 2018;Giri, Heckathorn, Mishra, & Krause, 2017). Here, mowing had a similar effect on the community but directly removed plant parts (photosynthetic product) rather than reducing the accumulation rate.…”
Section: Hws and Mowing Prolong Plant Phenologymentioning
confidence: 97%
“…Improving our understanding of the driving factors that control Aleppo pine responses to climatic conditions is important for managing the species and forecasting its responses to climate variability, extremes, and change. Relationships between various physiological traits and the abiotic environment have been reported in the literature for Aleppo pine [10][11][12]. Studies have demonstrated a strong stomatal regulation in the species and coordination between foliage water potential and stomatal conductance to balance water loss [13].…”
Section: Introductionmentioning
confidence: 99%